Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a) ĐK: \(x\ge0;x\ne1\)
Ta có: \(x-1=\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)\)
\(x+\sqrt{x}-2=\left(x-1\right)+\left(\sqrt{x}-1\right)=\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)\)
=> \(P=\frac{3\left(\sqrt{x}+1\right)+\sqrt{x}-3}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}:\frac{x+2-\sqrt{x}\left(\sqrt{x}-1\right)}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}\)
\(=\frac{4\sqrt{x}}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}:\frac{2+\sqrt{x}}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}\)
\(=\frac{4\sqrt{x}}{\sqrt{x}+1}\)
b) \(P=\sqrt{x}-1\)
<=> \(\frac{4\sqrt{x}}{\sqrt{x}+1}=\sqrt{x}-1\)
<=> \(x-4\sqrt{x}-1=0\)
<=> \(\orbr{\begin{cases}\sqrt{x}=2+\sqrt{5}\\\sqrt{x}=2-\sqrt{5}< 0\left(loại\right)\end{cases}}\)
<=> \(x=9+4\sqrt{5}\)thỏa mãn
![](https://rs.olm.vn/images/avt/0.png?1311)
\(M=\frac{3x+3\sqrt{x}-3}{x+\sqrt{x}-2}-\frac{\sqrt{x}+1}{\sqrt{x}+2}+\frac{\sqrt{x}-2}{\sqrt{x}}.\left(\frac{1}{1-\sqrt{x}}-1\right)\)
\(M=\frac{3x+3\sqrt{x}-3}{\left(\sqrt{x}+2\right)\left(\sqrt{x}-1\right)}-\frac{\left(\sqrt{x}+1\right)\left(\sqrt{x}-1\right)}{\left(\sqrt{x}+2\right)\left(\sqrt{x}-1\right)}\) \(+\frac{\sqrt{x}-2}{\sqrt{x}}.\frac{\sqrt{x}}{\sqrt{x}-1}\)
\(M=\frac{3x+3\sqrt{x}-3}{\left(\sqrt{x}+2\right)\left(\sqrt{x}-1\right)}-\frac{x-1}{\left(\sqrt{x}+2\right)\left(\sqrt{x}-1\right)}\) \(+\frac{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}\)
\(M=\frac{3x+3\sqrt{x}-3-x+1+x-4}{\left(\sqrt{x}+2\right)\left(\sqrt{x}-1\right)}\)
\(M=\frac{3x+3\sqrt{x}-6}{\left(\sqrt{x}+2\right)\left(\sqrt{x}-1\right)}\)
\(M=\frac{3\left(x+\sqrt{x}-2\right)}{x+\sqrt{x}-2}\)
\(M=3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
bài 2 : ĐKXĐ : \(x\ge0\) và \(x\ne1\)
Rút gọn :\(B=\frac{\sqrt{x}+1}{\sqrt{x}-1}-\frac{\sqrt{x}-1}{\sqrt{x}+1}-\frac{5\sqrt{x}-1}{x-1}\)
\(B=\frac{\left(\sqrt{x}+1\right)\left(\sqrt{x}+1\right)}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}-\frac{\left(\sqrt{x}-1\right)\left(\sqrt{x}-1\right)}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}-\frac{5\sqrt{x}-1}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}\)
\(B=\frac{x+2\sqrt{x}+1-x+2\sqrt{x}-1-5\sqrt{x}+1}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}\)
\(B=\frac{-\sqrt{x}+1}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}\)
\(B=\frac{-1}{\sqrt{x}+1}\)
\(B=\frac{\sqrt{x}\left(\sqrt{x}-1+\frac{1}{\sqrt{x}}\right)}{\sqrt{x}}=\sqrt{x}-1+\frac{1}{\sqrt{x}}=3+\frac{1}{\sqrt{x}}\Rightarrow\sqrt{x}=4\Leftrightarrow x=16\)
Vậy x=16 thì: \(\frac{x-\sqrt{x}+1}{\sqrt{x}}=3+\frac{1}{\sqrt{x}}\)